Precision heart rate training - Burke, Ed 1949-
This guide explains how to achieve peak fitness and performance with the help of a heart rate monitor. Leading authorities explain how to design and use training programmes for walking, running, cycling, in-line skating, multisport training, circuit training and group exercise